The food matters cookbook : 500 revolutionary recipes for better living - Bittman, Mark (Simon & Schuster, 2010)
This follow up to Mark Bittman's "NY Times" bestseller, "Food Matters: The Cookbook" offers around 450 recipes that will save your health and the planet.